Skala Kesadaran Gender Untuk Siswa Sekolah Dasar (SKG-SD) - Hanggara, Guruh S.; Arofah, Laelatul; Andrianie, Santy (Universitas Nusantara PGRI Kediri, 2020)
Gender awareness is an important competency in the development of elementary students as formulated in the SKKPD. A case of lack of gender awareness can be found in SD Negeri 1 Kolomayan 2 Blitar, where the level of gender awareness cannot be mapped. To be used as a mapping basis, this study aims to produce a Gender Awareness Scale (SKG-SD) for elementary school students that are valid in terms of content and construct. To achieve the desired research objectives, researchers used an instrument development design. The results obtained are SKG-PD with a content validity value of 1.00, which means very feasible. Furthermore, Cronbach's alpha items' analysis succeeded in filtering the SKG-SD items into only 16 items with a final reliability value of 0.879 in a very good and reliable category. Key Word: instruments, gender awareness scale, elementary school students